Electronic Properties of Acetaminophen Adsorbed on 2D Clusters: A First Principles Density Functional Study. Issue 13 (5th May 2017) - Saikia, Ujjal; Saikia, Nabanita; Waters, Kevin; Pandey, Ravindra; Sahariah, Munima Bora
Abstract: The interaction of acetaminophen (N‐acetyl‐para‐aminophenol), a prominent analgesic and antipyretic, with 2D clusters was investigated using density functional theory with inclusion of van der Waals dispersion correction. The implicit solvation model with three different solvents; water, ethanol and carbon tetrachloride were utilized to observe the trends in binding energy as a function of solvent polarity. The calculated results demonstrate that interactions are not solely dependent on solvent polarity, but inherent properties of the 2D clusters drive the nature of the interaction; i. e. physisorbed states were favored for graphene, boron nitride (BN), and phosphorene, whereas a chemisorbed state is preferred for silicene. Analysis of the frontier orbitals and density of states (DOS) show that the acetaminophen functionalization induces mid‐gap energy states in BN. Chemisorbed acetaminophen on silicene induces a 2p core level shift in silicon. The calculated results provide atomistic insights on the nature of interactions of acetaminophen with the new class of 2D materials beyond graphene for potential sensing applications. Abstract : A viable method for detection of acetaminophen, a prominent water‐borne contaminant in drinking water, is of prominent importance to meet environmental health standards. The interactions of acetaminophen with 2D materials namely graphene, phosphorene, silicene and boron nitride (BN) are investigated using the dispersion‐corrected DFT method. The calculated results are expected to facilitate the application of a new class of 2D materials beyond graphene as potential biosensors.